The prevalence of anxiety and fear in dental patients: A short study - Deepak Chaudhary; Shipra Saxena; Deviprasad Mahanta; Parul Yadav; Shoha H Patel; Sarita Agarwal; Karandeep Singh Arora (Wolters Kluwer Medknow Publications, 2020)
Background: Dental anxiety and fear are the major complications for both patient and dental care providers. The purpose of this study was to assess the prevalence of dental anxiety and fear in patients visiting the dental institute with respect to their gender. Materials and Methods: In the present study, 100 patients were provided with certain questionnaire which included two sections. The first section concerning age, gender, educational level, frequency of dental visits, reasons for irregular attendance, and existence of past traumatic experience. The second section comprises modified dental anxiety scale. Data was collected and analyzed with respect to gender using the statistical analysis. Results and Conclusion: Anxiety-associated dental treatment is widespread in the study population. Dental anxiety was higher in women and in the patients with traumatic dental experiences.